plz help me to find this plz pl
Attachments:
![](https://hi-static.z-dn.net/files/dfc/a08fb576df550c3a8f1da1b35354e3aa.jpg)
Answers
Answered by
1
1) M² - 2MN + N² - p²
![<b>a² - 2ab + b² = ( a - b )²</b> <b>a² - 2ab + b² = ( a - b )²</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3Ba%C2%B2+-+2ab+%2B+b%C2%B2+%3D+%28+a+-+b+%29%C2%B2%26lt%3B%2Fb%26gt%3B)
= ( M - N )² - p²
![<b>a² - b² = ( a + b ) ( a - b )</b> <b>a² - b² = ( a + b ) ( a - b )</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3Ba%C2%B2+-+b%C2%B2+%3D+%28+a+%2B+b+%29+%28+a+-+b+%29%26lt%3B%2Fb%26gt%3B)
= [ ( M - N ) + p ] [ ( M - N ) - p ]
= ( M - N + p ) ( M - N - p )
2) ( p + q )² - ( p - q )²
![<b>( a + b )² - ( a - b )² = 4ab</b> <b>( a + b )² - ( a - b )² = 4ab</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3B%28+a+%2B+b+%29%C2%B2+-+%28+a+-+b+%29%C2%B2+%3D+4ab%26lt%3B%2Fb%26gt%3B)
= 4pq
3) ( x + y )² - ( x - y )²
![<b>( a + b )² - ( a - b )² = 4ab</b> <b>( a + b )² - ( a - b )² = 4ab</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3B%28+a+%2B+b+%29%C2%B2+-+%28+a+-+b+%29%C2%B2+%3D+4ab%26lt%3B%2Fb%26gt%3B)
= 4xy
4) ax² + bx
Taking common
= x ( ax + b )
5) ( x + y )² - 4xy
![<b>( a + b )² - 4ab = ( a - b )²</b> <b>( a + b )² - 4ab = ( a - b )²</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3B%28+a+%2B+b+%29%C2%B2+-+4ab+%3D+%28+a+-+b+%29%C2%B2%26lt%3B%2Fb%26gt%3B)
= ( x - y )²
6) ( a + b )² - 4ab
![<b>( x + y )² - 4xy = ( x - y )²</b> <b>( x + y )² - 4xy = ( x - y )²</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3B%28+x+%2B+y+%29%C2%B2+-+4xy+%3D+%28+x+-+y+%29%C2%B2%26lt%3B%2Fb%26gt%3B)
= ( a - b )²
7) ( p² - 2pq + q² ) - r²
![<b>( a² - 2ab + b² ) = ( a - b )²</b> <b>( a² - 2ab + b² ) = ( a - b )²</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3B%28+a%C2%B2+-+2ab+%2B+b%C2%B2+%29+%3D+%28+a+-+b+%29%C2%B2%26lt%3B%2Fb%26gt%3B)
= ( p - q )² - r²
= ( p - q )² - ( r )²
![<b>a² - b² = ( a + b ) ( a - b )</b> <b>a² - b² = ( a + b ) ( a - b )</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3Ba%C2%B2+-+b%C2%B2+%3D+%28+a+%2B+b+%29+%28+a+-+b+%29%26lt%3B%2Fb%26gt%3B)
= [ ( p - q ) + r ] [ ( p - q ) - r ]
= ( p - q + r ) ( p - q - r )
8) 49p² - 36q² + 12qr - r²
= ( 7p )² - ( 6q )² + 12qr - r²
![<b>a² + b² = ( a + b ) ( a - b )</b> <b>a² + b² = ( a + b ) ( a - b )</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3Ba%C2%B2+%2B+b%C2%B2+%3D+%28+a+%2B+b+%29+%28+a+-+b+%29%26lt%3B%2Fb%26gt%3B)
= ( 7p + 6q ) ( 7p - 6q ) + 12qr - r²
9) ( M + N )² - ( M - N )²
![<b>( a + b )² - ( a - b )² = 4ab</b> <b>( a + b )² - ( a - b )² = 4ab</b>](https://tex.z-dn.net/?f=%26lt%3Bb%26gt%3B%28+a+%2B+b+%29%C2%B2+-+%28+a+-+b+%29%C2%B2+%3D+4ab%26lt%3B%2Fb%26gt%3B)
= 4MN
= ( M - N )² - p²
= [ ( M - N ) + p ] [ ( M - N ) - p ]
= ( M - N + p ) ( M - N - p )
2) ( p + q )² - ( p - q )²
= 4pq
3) ( x + y )² - ( x - y )²
= 4xy
4) ax² + bx
Taking common
= x ( ax + b )
5) ( x + y )² - 4xy
= ( x - y )²
6) ( a + b )² - 4ab
= ( a - b )²
7) ( p² - 2pq + q² ) - r²
= ( p - q )² - r²
= ( p - q )² - ( r )²
= [ ( p - q ) + r ] [ ( p - q ) - r ]
= ( p - q + r ) ( p - q - r )
8) 49p² - 36q² + 12qr - r²
= ( 7p )² - ( 6q )² + 12qr - r²
= ( 7p + 6q ) ( 7p - 6q ) + 12qr - r²
9) ( M + N )² - ( M - N )²
= 4MN
Similar questions
Math,
8 months ago
Computer Science,
8 months ago
Political Science,
8 months ago
English,
1 year ago
Math,
1 year ago